Pentingnya Pendidikan Ekonomi untuk Terwujudnya Pengelolaan Keuangan Rumah Tangga yang Baik - Nuryadin, Muhammad Birusman (SYAMIL, 2014)
An author had watched a phonemenon, that is a complaint of ladies community which was caused by their husbandsâ misunderstanding in managing an economy household. Finally there was nervousness, commotion and misharmony in a family. Watching that phenomenon made the author think that economics education is very important to change a character and behavior in order to be able to manage the household economy well. There are some theories about a needs related to management of household economy, one of those theories is a theory of Maslow. According to this theory, a fulfillment of household needs must be done by priority scale. It is not suggested to fulfill a higher need while a lower need has not neen fulfilled. If that case can be implemented well, it wauld be a factor in forming a family of Sakinah mawaddah wa rohmah